In Silico Study of Compounds Identified in Curcuma aeruginosa Roxb Rhizome as BRAF V600E Inhibitors in Melanoma Cancer - Suharsanti, Ririn; Ryan Radix Rahardhian, Muhammad; Kusmita, Lia (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Curcuma aeruginosa Roxb rhizome contains secondary metabolite compounds and plays a role in various activities such as antioxidant, antibacterial, anthelmintic, antiandrogenic, antinociceptive, and anticancer. Anticancer activity that has been reported in Curcuma aeruginosa Roxb rhizome is limited to breast and cervical cancer. The purpose of this study was to explore the potential of Curcuma aeruginosa Roxb rhizome in melanoma cancer through the mechanism of inhibiting the BRAF V600E. The 96% ethanol extract of Curcuma aeruginosa Roxb rhizome was separated to produce n-hexane (HF), ethyl acetate (EAF), and ethanol (EF) fractions. The GC-MS results showed that there were 31 compounds from the three fractions. The docking validation process was carried out on the native ligand N-(3-[5-(4-chlorophenyl) -1H-pyrrolo [2,3b]pyridin3yl] carbonyl2,4difluorophenyl) propane-1-sulfonamide. All compounds were prepared as ligands for molecular docking with the BRAF V600E receptor (PDB ID: 3OG7). Docking validation on native ligand showed RMSD 1.03Å. The smallest binding affinity are 4,4a,5,6,7,8-Hexahydronaphthalen-2(3H)-one (-6,89 kcal/mol); 1Cyclohexyl-2-propen-1-one (-6,68 kcal/mol); Cyclooctenone (-6,23 kcal/mol); and vemuravnib is still better as K+ (-11.11 kcal/mol). All three compounds do not bind to key amino acid residues of BRAF V600E such as vemuravenib at GLN A:530, CYS A:532; ASP A:594. These results indicate that further structural development is needed for better activity.